Fabrication and Specific Functionalisation of Carbon Fibers for Advanced Flexible Biosensors - Wenrui, Zhang; Fanxing, Meng; Yanan, Qin; Fei, Chen; Haitao, Yue; Minwei, Zhang (Frontiers in Chemistry, 2020)
This review aims at offering an up-to-date comprehensive summary of carbon fibers (CFs)-based composites, with the emphasis on smart assembly and purpose-driven specific functionalization for their critical applications associated with flexible sensors. We first give a brief introduction to CFs as a versatile building block for preparation of mutil-fountional materials and the current status of research studies on CFs. This is followed by addressing some crucial methods of preparation of CFs. We then summarize multiple possibilities of functionalising CFs, an evaluation of some key applications of CFs in the areas of flexible biosensors was also carried out.